Students’ Creativity in Solving Mathematical Problems through Problem Based Learning - Farrah Maulidia; Rahmah Johar; Andariah Andariah (Proceedings of AICS - Social Sciences, 2017)
Creativity could be interpreted as a person's cognitive abilities in solving problems by bringing up new ideas. The students’ math inadequate achievement is motivated by the fact that math presented as finished product, ready to use, abstract and taught mechanistic. This case can be lead to the creativity of the less developed students because students are not given the opportunity to think and use their ideas in solving mathematical problems. Problem Based Learning Model is a learning model that emphasizes the concept and information outlined from the academic discipline. The purpose of this study is to analyzed students’ creativity in solving mathematical problems through Problem Based Learning model (PBL) in class VIII-1 MTsN Model Banda Aceh. Data were gained based on the students’ worksheet in groups. The data acquisition is categorized into 5 levels (4 as the highest level and 0 as the lowest level) which is analyzed descriptively. The results show that three groups were at level 4 with very creative category, one group is at level 3 with creative category and the other group is at level 2 with deeply creative enough category. To conclude, PBL model could increase the students’ creativity in solving mathematical problems. Keywords: mathematical creativity, problem based learning.